PEMAKNAAN AYAT MENURUT HARUN NASUTION DALAM BUKU ISLAM DITINJAU DARI BERBAGAI ASPEKNYA - Humaidi, Riki; Alkadri, Alkadri; Sunandar, Sunandar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Harun Nasution is a Muslim scholar who was able to change the exclusive perspective of Islam to an inclusive one, as evidenced by the market acceptance of the book